Introdução de quantidades efetivas para o estudo da sincronização e criptografia baseada em sistemas não-síncronos - Szmoski, Romeu Miquéias (2013)
Synchronization is a dynamical behavior exhibited by a wide range of systems. Neurons, firefly and Josephson junctions are examples of these systems. It is defined as an adjustment of rhythms of oscillating objects due to weak interaction between them, and it is studied using different mathematical models including the coupled map lattices (CMLs). In CML the synchronization corresponds to process in which all state variables become identical at the same instant. Usually we study the CML synchronization by calculating the conditional Lyapunov exponents. However, if the coupling or network topology is time-varying, this exponents are not readily determined. In this work we propose new quantities to study the synchronization in these CMLs. These quantities are defined as weighted averages over all possible topologies and, if the topology is constant, they are equivalent to the usual Lyapunov exponents. We find an analytical expression for the effective quantities when the topology is invariant over translation on the network and demonstrate that an ensemble of short time observations can be used to predict the long-term behavior of the lattice. Also we point that, if network has constant and homogeneous structure, the effective quantities correspond to the projection on the eigenvectors associated with this structure. We show the availability of effective quantities using them to build a lattice with constant topology that exhibits the same synchronization critical properties of the lattice with time-varying topology. Finally, we present a cryptosystem for communication systems based on two replica synchronized networks whose elements are not synchronous. We investigate it as to operation time, robustness and security against intruders. Our results suggest that it is safe and efficient for a wide range of parameters.